The experimental and numerical investigation on a hybrid battery thermal management system based on forced-air convection and internal finned structure. (August 2021) - Qin, Peng; Liao, Mengran; Mei, Wenxi; Sun, Jinhua; Wang, Qingsong
Highlights: A thermal management system is designed for electrochemical energy storage. A hybrid thermal management system is proposed based on internal finned structure. The effectiveness is proved experimentally with the cycling rate of 1 C to 4 C. Various influential factors are investigated based on mathematical modeling. Abstract: Thermal management is crucial for the lifespan and safety of lithium-ion batteries, especially for the electrochemical energy storage which is composed of thousands of battery cells. In this paper, a novel battery thermal management system (BTMS) with internal finned structure was first proposed based on forced-air convection for the cylindrical battery pack in the field of electrochemical energy storage. The proposed battery thermal management system combined the advantages of forced-air convection and internal finned structure, capable of well managing the maximum temperature and the maximum temperature of the cylindrical battery pack. The experimental results of this study revealed that the internal finned structure improved the temperature uniformity and forced-air convection reduced the maximum temperature. Even though the battery pack operated under the 4 C rate, the maximum temperature and the maximum temperature difference are well controlled below 48.5 ℃ and 4.8 ℃. Moreover, a mathematical model was established. After its results were validated by experiments, it was used to analyze the effect of the gap space, ambient temperature, and finned material on the cooling performance. The numerical findings provided insights into the application of the proposed battery thermal management system. In practice, the gap space of aluminum finned structure should be set as 4 mm, and the cycling rate should be no more than 3 C at ambient temperature over 25 °C.